Egypt and Serbia: rich history and bright shared future - Salah, Bassel (Napredak, 2022)
Egypt and Serbia have maintained diplomatic relations ever since their establishment between the Khedivate of Egypt and the Kingdom of Serbia in 1908. Next year will the 115th anniversary since the beginning of the diplomatic relations between these two friend states. Both countries have excellent relations, although there is a huge space for improving bilateral cooperation in many areas. Exceptional relations between Egypt and Serbia are founded on strong connections from recent history, which are deeply rooted in characteristic and identical views of the future of their countries and nations, and the goals to be achieved. These relations were particularly developed during the presidential mandates of Naser and Tito, because these two countries, due to their significant role in the formation of the Non-Aligned Movement, cooperated for the welfare of the entire independent and free world.